Effect of hydro-alcoholic extract of Rosa damascena on cardiovascular responses in normotensive rat - Mohammad Naser Shafei; Amir Baniasad; Abolfazl Khajavirad; Mahmoud Hosseini; Saeed Aminzadah; Mahmoud Ghavi (Mashhad University of Medical Sciences, 2015)
Objective: Rosa damascena mill L. (R. damascena) is a well-known plant with fragrant effects. Several therapeutic effects of this plant on respiratory, gastrointestinal and nervous systems have been reported. It is also suggested to have beneficial effect on cardiovascular system especially blood pressure regulation. The present study was carried out to evaluate acute cardiovascular effect of hydro-alcoholic extract of R. damascena. Materials and Methods: Thirty-two male Wistar rats were randomly divided into four groups (n= 8 for each group). After anesthesia, a catheter was inserted into the femoral artery and blood pressure and heart rate (HR) were continuously recorded by a power lab system. Animals received three doses of hydro-alcoholic extract (250, 500, and 1000 mg/kg) via peritoneal (i.p). After 30 min, systolic blood pressure (SBP), mean arterial pressure (MAP) and HR were recorded and maximal changes were compared to control group. Results: Injection of all doses of the extract did not significantly change HR compare to control group. The SBP, dose dependently, was decreased by all doses of the extract and the maximal response was significant compared to saline group (p Conclusion: This study provides evidence of a hypotensive effect of hydro-alcoholic extract of R. damascena with no significant effect on HR. Therefore, R. damascena is suggested to have beneficial effect to control blood pressure. However, it needs to be more investigated.